2018
DOI: 10.1007/s10068-018-0458-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant capacity of 4-vinylguaiacol with catechin and ferulic acid in oil-in-water emulsion

Abstract: The product of ferulic acid decarboxylation, 4-vinylguaiacol (4-VG), is an important antioxidant and is reported to have an antioxidant capacity comparable to atocopherol. In this study, evaluation on antioxidant capacities of ferulic acid, catechin, and 4-VG was performed when 200 ppm of each compound was added in a 10% O/W emulsion for 50 days. Peroxide value (POV) results of the O/W emulsion containing 4-VG were noteworthy. The POV was 1.9 meq/L of emulsion after 29 days, which was no different to the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Humulene epoxide is also a moderate antioxidant [ 39 ]. The 2-Mwthoxy-4-vinylphenol i.e., p-Vinylguaiacol is a significant radical scavenger [ 40 , 41 ]. As far as the (+)-ascorbic acid 2,6- dihexadecanoate is concerned, this is used as a reference standard in free radicals scavenging activities [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humulene epoxide is also a moderate antioxidant [ 39 ]. The 2-Mwthoxy-4-vinylphenol i.e., p-Vinylguaiacol is a significant radical scavenger [ 40 , 41 ]. As far as the (+)-ascorbic acid 2,6- dihexadecanoate is concerned, this is used as a reference standard in free radicals scavenging activities [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a certain body of literature evidence claiming clear antioxidant effects of FA in various o/w systems including: (i) corn oil-based emulsions stabilised with the use of various emulsifiers [56]; (ii) Tween-linoleic acid-based emulsions [14] (iii) in Tween-menhaden o/w emulsions [57]. More recently, Shin et al (2019) [58] reported that 4-vinylguaiacol (4-VG), (product of FA decarboxylation), exerted a strong antioxidant activity when added at 200 ppm in a 10% o/w emulsion for 50 days. Permin et al (2019) [59], however, reported that FA showed no antioxidant activity in o/w emulsions rich in ω-3 fatty acids and stabilised by whey proteins.…”
Section: Ferulic Acid (Fa)mentioning
confidence: 99%
“…CA exerted a clear antioxidant effect when added in o/w emulsion systems stabilised by Tween and prepared with various vegetable oils [46,47]. Ferulic acid (FA) is another phenolic acid -commonly present in many plant seeds [48] that was reported to act as a strong antioxidant following its addition in a range of oil-based emulsions [49][50][51].…”
Section: Overview Of Studies Reporting On the Effect Of Phenolics Aga...mentioning
confidence: 99%